2019
DOI: 10.1093/scan/nsz055
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of neuroimaging studies on pain empathy: investigating the role of visual information and observers’ perspective

Abstract: Empathy relies on brain systems that support the interaction between an observer’s mental state and cues about the others’ experience. Beyond the core brain areas typically activated in pain empathy studies (insular and anterior cingulate cortices), the diversity of paradigms used may reveal secondary networks that subserve other more specific processes. A coordinate-based meta-analysis of fMRI experiments on pain empathy was conducted to obtain activation likelihood estimates along three factors and seven con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
142
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(165 citation statements)
references
References 173 publications
(179 reference statements)
22
142
0
1
Order By: Relevance
“…The idea that vicarious pain across different induction procedures shares common neural representations has been supported by meta-analyses covering previous fMRI pain empathy studies that demonstrated overlapping activation in the insular and cingulate cortex 3,9 . Consistent with these meta-analytic findings we found that these regions were consistently engaged during both physical and affective vicarious pain.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The idea that vicarious pain across different induction procedures shares common neural representations has been supported by meta-analyses covering previous fMRI pain empathy studies that demonstrated overlapping activation in the insular and cingulate cortex 3,9 . Consistent with these meta-analytic findings we found that these regions were consistently engaged during both physical and affective vicarious pain.…”
Section: Discussionmentioning
confidence: 96%
“…refs. 3,9 ). However, the conventional univariate approach lacks anatomical and functional specificity to test the question of whether vicarious pain across different modalities shares common and process-specific neural representations 10,25,27,43 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations